Absorptive capacity and mass customization capability. Issue 9 (7th September 2015) - Brian Fynes; Professor Paul Coughlan, Professor; Zhang, Min; Zhao, Xiande; Lyles, Marjorie A.; Guo, Hangfei
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effects of a manufacturer's absorptive capacity (AC) on its mass customization capability (MCC). Design/methodology/approach – The authors conceptualize AC within the supply chain context as four processes: knowledge acquisition from customers, knowledge acquisition from suppliers, knowledge assimilation, and knowledge application. The authors then propose and empirically test a model on the relationships among AC processes and MCC using structural equation modeling and data collected from 276 manufacturing firms in China. Findings – The results show that AC significantly improves MCC. In particular, knowledge sourced from customers and suppliers enhances MCC in three ways: directly, indirectly through knowledge application, and indirectly through knowledge assimilation and application. The study also finds that knowledge acquisition significantly enhances knowledge assimilation and knowledge application, and that knowledge assimilation leads to knowledge application. Originality/value – This study provides empirical evidence of the effects of AC processes on MCC. It also indicates the relationships among AC processes. Moreover, it reveals the mechanisms through which knowledge sourced from customers and suppliers contributes to MCC development, and demonstrates the importance of internal knowledge management practices in exploiting knowledge from supply chain partners. Furthermore, it provides guidelines for executives to decide how to manage supply chain knowledge and devote their efforts and resources in absorbing new knowledge for MCC development.